Strategi Fundraisang Dan Distribusi Dana Zis Di LAZ Sidogiri Cabang Banyuwangi - Munawir Munawir; Imam Husnudin; Nur Kholis (Journal of Islamic Banking, 2022)
The purpose of this study is to find out how the fundraisang strategy and distribution of zakat, infaq, and alms funds at the Amil Zakat Institute Sidogiri Banyuwangi branch and find out what are the supporting factors and inhibiting factors of the fundraisang strategy and distribution of zakat funds. infaq, and alms at the Amil Zakat Institute Sidogiri Banyuwangi branch. This research is in the form of field research with qualitative research methods. Data collection techniques in the form of interviews, observations, and documentation. The source of research data comes from primary data and secondary data. The data analysis tool uses an interactive analysis model. The results of this study are 1) The fundraising strategy at LAZ Sidogiri Banyuwangi branch is carried out by funding prospective donors. then a withdrawal agreement was made by FO LAZ Sidogiri Banyuwangi branch with donors. The ZIS fund distribution strategy at LAZ Sidogiri Banyuwangi branch follows the branch leadership meeting every year with a consumptive and productive distribution mechanism. 2) The supporting factors of the ZIS fundraisang and distribution strategy at LAZ Sidogiri are communication, and Sidogiri branding. The inhibiting factors are HR, Accountability, and the very heavy policy of Law No.23 of 2011. The conclusion of this study is, LAZ Sidogiri as an institution that serves as an institution that collects and manages zakat, infaq, and alms funds, in accordance with Law Number 23 of 2011 Article 11.